Laser-assisted leather punch technique for the management of aural haematoma in dogs - Kaushal, Sara; Kumar, Adarsh; Kumar, Rohit; Kumar, Amit; Thakur, Kalpna; Mahabalesh, Sankalp; Thakur, Sidharth Singh; Tyagi, S.P. (Indian Journal of Veterinary Surgery, 2025)
Thirteen dogs presented with aural haematoma were used in this study. All the patients were managed by the use of a laserassisted leather punch technique under general anaesthesia. The CO2 laser was used to make 2 circular incisions on the concave surface of the ear. The haematoma was drained and the cavity was flushed. Multiple small focal tissue welding incisions were made to stimulate adhesion between the tissue layers. Postoperatively pressure bandaging along with standard care was observed. Haematoma was resolved in all the cases within a time period of 10-15 days without recurrence. The leather punch technique using CO2 laser resulted in quick (8-14 days) healing with minimal scarring and contracture of pinna.